The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1590/s1678-9946201860044
|View full text |Cite
|
Sign up to set email alerts
|

Study of Aedes aegypti population with emphasis on the gonotrophic cycle length and identification of arboviruses: implications for vector management in cemeteries

Abstract: Aedes aegypti is the vector of the arboviruses causing dengue, chikungunya and zika infections in Mexico. However, its presence in public places has not been fully evaluated. In a cemetery from Merida, Yucatan, Mexico, the productivity of Ae. aegypti, the gonotrophic cycle, and the presence of Ae. aegypti females infected with arboviruses were evaluated. Immature and adult mosquitoes were inspected every two months between April 2016 to June 2017. For the gonotrophic cycle length, the daily pattern of total an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 34 publications
(57 reference statements)
0
10
1
Order By: Relevance
“…The results in this study show a higher infection rate by DENV-1 and CHIKV in A. albopictus (Table 2) compared to A. aegypti. This does not agree with the values previously reported since the MIR values in A. aegypti are higher (Guerbois et al, 2016;Huerta et al, 2017;Garcia-Rejon et al, 2018). However, it was experimentally shown that A. albopictus is a vector more susceptible to infection than A. aegypti because the arbovirus dissemination rates were higher in nearly all strains of A. albopictus tested (Turell et al, 1992).…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…The results in this study show a higher infection rate by DENV-1 and CHIKV in A. albopictus (Table 2) compared to A. aegypti. This does not agree with the values previously reported since the MIR values in A. aegypti are higher (Guerbois et al, 2016;Huerta et al, 2017;Garcia-Rejon et al, 2018). However, it was experimentally shown that A. albopictus is a vector more susceptible to infection than A. aegypti because the arbovirus dissemination rates were higher in nearly all strains of A. albopictus tested (Turell et al, 1992).…”
Section: Discussioncontrasting
confidence: 73%
“…Alternatively, ZIKV has a MIR value ranging from 3 to 17 individuals and CHIKV ranges from 2 to 3 individuals. Finally, for MAYV, the only reported value is 1.75 (Diallo et al, 2014;Guerbois et al, 2016;Huerta et al, 2017;Cevallos et al, 2018;Eiras et al, 2018;Garcia-Rejon et al, 2018). These data show that A. aegypti presents a higher rate of natural infection by arboviruses compared to A. albopictus and this is attributed to the greater presence of this species in urban areas, which indicates that A. aegypti is the main vector of arboviruses and A. albopictus is the secondary vector in Latin America (Black et al, 2002;Paupy et al, 2009).…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Previous studies performed in Merida identified DENV-infected Ae. aegypti in schools 9 and a cemetery 31 . DENV- and ZIKV-infected Ae.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Devera et al [9] found only two mosquito genera: Aedes and Culex in Ciudad Bolívar, Venezuela; Castillo et al [22] reported only immature stages of Ae. aegypti in the three inspected cemeteries in Trujillo, Venezuela; Garcia‐Rejon et al [25] found Ae. aegypti , Cx.…”
Section: Discussionmentioning
confidence: 99%